Fort-de-France et Pointe-à-Pitre : deux villes américaines ? - Christophe Charlery (In Situ)
We will follow the process of dissemination of a standard type of building that was developed in England during the 18th century and that spread from 1790 to the 1820’s along the East Coast of the former Anglo–American colonies, between Boston and New Orleans. It is in the latter city that this style of architecture underwent the first instance of creolization, before becoming widespread, between 1840 and 1850, in certain cities of the West Indies, among them Fort–de–France in Martinique and Pointe–à–Pitre in Guadeloupe. A second process of creolization allowed the creation of new designs that established a distinctive identity to these two West Indian cities of French origin.